The Impact Of Leadership Behavior On The Business Growth Through The Organizational Innovation And Managerial Practices - Rafiq, Muhammad; Haris, Muhammad; Anwar, Malik Javied; Majeed, Kashif Bilal (Archives of Business Research, 2017)
The main objective of this empirical study is to determine the affect of leadership behavior with the organizational innovative techniques and managerial practices on the businesses’ growth in Pakistan particularly in textile sector. Firstly, the study discusses the relationship between leadership behavior and organizational innovation, between organizational behavior and managerial practices. Furthermore, this relationship is also measured between organizational innovation and business growth and between managerial practices and business growth. Secondly, the study investigates that these relationship are strongly reinforced in the firm with the support of theoretical evidences made but not determined theoretically in the prior literature. Managerial practices take place in textile community for interaction in which organizational cognition is developed and expanded dynamically between the cognitive and behavioral changes. Organizations with greater organizational acquisition and practices create a learning network that will become easier to learn that what they use to learn and to initiate, enabling the firm to preserve its effective and competitive aversion as a textile technological center. Nomothetic research method is applied to test the hypothesis, developed for this study. The research examined a sample of one hundred ten textile firms with sample unit of senior managers, executives, administrative and other-level managers. A research model is formulated for the study and hypotheses are tested with the use of structural equation model. This study purposes that the leaders of firms initiate a transformational role, which facilitate organizational innovation and managerial performances and consequently enhance the business growth especially in textile firms.